2021
DOI: 10.3758/s13421-021-01187-w
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime sleep benefits the prospective component of prospective memory

Abstract: Studies suggest that sleep benefits event-based prospective memory, which involves carrying out intentions when particular events occur. Prospective memory has a prospective component (remembering that one has an intention), and a retrospective component (remembering when to carry it out). As effects of sleep on retrospective memory are well established, the effect of sleep on prospective memory may thus be due exclusively to an effect of sleep on its retrospective component. Therefore, the authors investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Using the sleep deprivation paradigm, several studies have shed light on the detrimental effect of sleep loss on the ability to perform an intended action at the appropriate times [ 21 , 22 , 23 , 24 ]. Sleep deprivation significantly affects ProM through the involvement of specific brain areas, in particular the prefrontal cortex [ 25 ], strongly involved in executive and control processes.…”
Section: Introductionmentioning
confidence: 99%
“…Using the sleep deprivation paradigm, several studies have shed light on the detrimental effect of sleep loss on the ability to perform an intended action at the appropriate times [ 21 , 22 , 23 , 24 ]. Sleep deprivation significantly affects ProM through the involvement of specific brain areas, in particular the prefrontal cortex [ 25 ], strongly involved in executive and control processes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that people who sleep better usually also perform better in prospective memory, suggesting a potential link between prospective memory and sleep. [2] So prospective memory is a factor that has been found to impact sleep quality significantly. With this possible link, studying the relationship between prospective memory and sleep quality could help us provide insights and comments on improving daytime performance and sleep patterns and promoting health.…”
Section: Introductionmentioning
confidence: 99%